2021
DOI: 10.22270/jddt.v11i6.5037
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Various Concentrations of Ethanol Extract of the Leaves of Paederia foetida L. on the Growth of Escherichia Coli Bacteria

Abstract: Bacterial infection of Escherichia coli (E. coli) as the cause of gastrointestinal disorders in humans has increased their prevalence. Treatment using natural ingredients can be a choice of therapy because of the minimal side effects. One of the rare plants believed by the community as an antibacterial is stinking vin’e known as the ‘leaf fart’. The purpose of this research is for knowing the activity of the ethanol extract of Paederia foetida L can affect the growth of E.coli. The serial diffusion disc method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 6 publications
0
0
0
Order By: Relevance
“…The results of phytochemical test on P. foetida leaves previously revealed that this plant contains alkaloids, tannins, flavonoids, phenol, terpenoid, saponin, and cardiac glycosides (Upadhyaya 2013), thus could be able to inhibit S. aureus and Bacillus subtilis. Another study conducted by (Silaban 2021) revealed that the ethanol extract of P. foetida leaves successfully inhibited the growth of E. coli.…”
Section: Introductionmentioning
confidence: 99%
“…The results of phytochemical test on P. foetida leaves previously revealed that this plant contains alkaloids, tannins, flavonoids, phenol, terpenoid, saponin, and cardiac glycosides (Upadhyaya 2013), thus could be able to inhibit S. aureus and Bacillus subtilis. Another study conducted by (Silaban 2021) revealed that the ethanol extract of P. foetida leaves successfully inhibited the growth of E. coli.…”
Section: Introductionmentioning
confidence: 99%